Elegies and Laments in the Nova Scotia Gaelic Song Tradition: Conservatism and Innovation - Robert Douglas Dunbar (Genealogy, 2021)
Gaelic-speaking emigrants brought with them a massive body of oral tradition, including a rich and varied corpus of song–poetry, and many of the emigrants were themselves highly skilled song-makers. Elegies were a particularly prominent genre that formed a crucially important aspect of the sizeable amount of panegyric verse for members of the Gaelic aristocracy, which is a tradition dating back to the Middle Ages. This contribution will demonstrate that elegies retained a prominent place in the Gaelic tradition in the new world Gaelic communities established in many parts of Canada and in particular in eastern Nova Scotia. In many respects, the tradition is a conservative one: there are strong elements of continuity. One important difference is the subjects for whom elegies were composed: in the new world context, praise for clan chiefs and other members of the traditional Gaelic aristocracy were no longer of relevance, although a small number were composed primarily out of a sense of personal obligation for patronage shown in the Old Country. Instead—and as was increasingly happening in the nineteenth century in Scotland, as well—the deaths of new community leaders, including clergy, and other prominent Gaels were recorded in verse. The large number of songs composed to mark the deaths of community members is also important—particularly young people lost at sea and in other tragic circumstances, occasionally in military service, and so forth. In these song–poems, we see local poets playing a role assumed by song-makers throughout Gaelic-speaking Scotland and Ireland: that of spokespeople for the community as a whole.